Efficacy of Super-Bioavailable Itraconazole and Conventional Itraconazole at Different Dosing Regimens in Glabrous Tinea Infection - A Randomized Clinical Trial [Corrigendum] - Shenoy MM; De A; Shah B; Das A; Saraswat A; Lahiri K; Yadav S; Sarda A; Chakraborty D; J D; Kamat S; Doshi Y; et al. (Dove Medical Press, 2023)
Shenoy MM, De A, Shah B, et al. Drug Des Devel Ther. 2023;17:2899-2908. The authors have advised the affiliation indicators in the author list on page 2899 is incorrect. The correct author list and affiliations are as follows. Manjunath M Shenoy1, Abhishek De2, Bela Shah3, Anupam Das4, Abir Saraswat5, Koushik Lahiri2, Sheetal Yadav6, Aarti Sarda2, Disha Chakraborty7, Dharmender J3, Shruti Kamat3, Yashika Doshi3, Nelry Gonsalves3, Ankita Choudhary3, Dhiraj Dhoot8, Namrata Mahadkar8, Sumit Bhushan8, Rujuta Gadkari8, Hanmant Barkate8 1Department of Dermatology, Omega Hospital, Mangalore, Karnataka, India; 2Department of Dermatology, Wizderm Specialty Skin and Hair Clinic, Kolkata, West Bengal, India; 3Department of Dermatology, BJ Medical College and Civil Hospital, Ahmedabad, Gujarat, India; 4Department of Dermatology, Iris Multispecialty Hospital, Kolkata, West Bengal, India; 5Department of Dermatology, Indushree Skin Clinic, Lucknow, Uttar Pradesh, India; 6Department of Dermatology, ABVIMS and Dr. RML Hospital, New Delhi, India; 7Department of Dermatology, Calcutta National Medical College, Kolkata, West Bengal, India; 8Department of Global Medical Affairs, Glenmark Pharmaceuticals Ltd, Mumbai, Maharashtra, India The authors apologize for this error.